Supervision of local government to village regulation in regional autonomy are reviewed theory - Putra Astomo (Indonesia Prime, 2017)
The Law Number 6 of 2014 years and PP Number 43 of 2014 years are law product which to rule supervision of local government to village regulation in regional autonomy are reviewed. PP Number 43 of 2014 years reads that the technical guidelines on the rules in the village are set by regulation, so which mandates the need for regulation as a regulatory technical guidelines in the village, it also formed Minister Regulation Number 111 of 2014 years about Technical Guidelines Rules In the Village. The method that is used the approach of law (statute approach). This method is done by examining all the legislation and regulations relevant to the legal issues being addressed. The result of this research are supervision is done in two forms, including evaluation and clarification. It was concluded supervision of local government to village regulation in regional autonomy are reviewed as stipulated in Minister Regulation Number 111 of 2014 years are done in two forms, including evaluation and clarification.